Embedding Ethical AI in Digital Public Infrastructure: Strategic Governance Pathways for Indonesia - Bachtiar, Goutama (PT Penjaminan Infrastruktur Indonesia (Persero), 2025)
Indonesia’s accelerating digital transformation, driven by programs such as Digital ID and INA Digital, has introduced both significant opportunities and complex governance challenges as Artificial Intelligence (AI) becomes integrated into public-sector decision-making. This conceptual paper proposes a strategic governance framework for ethical AI that aligns international standards such as the OECD AI Principles, the EU AI Act, and the NIST AI Risk Management Framework with Indonesia’s institutional and regulatory environment. The study contributes to the literature by articulating a policy-oriented model operationalizing ethics, transparency, and accountability within the national digital ecosystem. It further demonstrates how anticipatory governance, multistakeholder collaboration, and adaptive regulation can be embedded through ongoing programs led by the Ministry of Communication and Digital (Komdigi), BSSN, and BRIN. By linking global frameworks with local implementation pathways, this research provides conceptual advancement and policy relevance for emerging economies seeking to institutionalize trustworthy AI governance.